Coupled Biosynthesis of Volatiles and Salinosporamide A in Salinispora tropica. (6th September 2016) - Groenhagen, Ulrike; Leandrini De Oliveira, Ana Ligia; Fielding, Elisha; Moore, Bradley S.; Schulz, Stefan
Abstract: Terrestrial bacteria, especially actinomycetes, are known to be prolific producers of volatile compounds. We show here that bacteria from ocean sediments can also release complex bouquets of volatiles. The actinomycete Salinispora tropica produces cyclohexenyl compounds not previously known in nature, such as methyl cyclohex‐2‐ene‐1‐carboxylate (9 ), methyl 2‐(cyclohex‐2‐en‐1‐yl)acetate (10 ), methyl ( E / Z )‐2‐(cyclohex‐2‐en‐1‐ylidene)acetate (11 /12 ), and related alcohols8 and13 . These compounds were identified by GC/MS and confirmed by synthesis. In addition, rare spiroacetals, aromatic compounds, short‐chain acids and esters, alcohols, and various cyclic compounds were produced by the bacteria. The biosynthesis of the cyclohexenyl compounds is closely coupled to that of cyclohexenylalanine (4 ), a building block of salinosporamide A, a proteasome inhibitor produced by S. tropi ca. Analysis of S. tropica strains that harbor knockouts of the salinosporamide biosynthetic genes salX and salD, coupled with feeding experiments, revealed that 3‐(cyclohex‐2‐en‐1‐yl)‐2‐oxopropanoic acid (60 ) and 3‐(cyclohex‐2‐en‐1‐ylidene)‐2‐oxopropanoic acid (isomers61 and62 ) are important intermediates in the biosynthesis of salinosporamide A, 4, and8 –13 . Abstract : The marine sediment bacterium Salinispora tropica produces not only the proteasome inhibitor salinosporamide A, but at the same time a plethora of volatile compounds. Mutant feeding experiments showed that biosynthesis of the major volatile cyclohexenyl derivatives is closely connected to the biosynthesis of cyclohexenylalanine, a building block of salinosporamide.